1979
DOI: 10.1136/pgmj.55.641.180
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid, neutral sterol and faecal fat excretion in subjects treated with fenfluramine and its relationship to fenfluramine-induced diarrhoea

Abstract: SummaryBile acid, neutral sterol and faecal fat excretion was studied over a period of 9 weeks in a group of 16 healthy subjects before, during and after administration of fenfluramine. Statistical analysis revealed a significant increase in bile acid excretion during the drug phase (P<0.02); and during recovery period of 3 weeks (P< 0-05). Faecal neutral sterol, as the total of coprostanol and cholesterol elimination was also enhanced after fenfluramine. Coprostanol was replaced by cholesterol in 12 subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This will give similar results, but will prevent the potential formation ofbile acid ethyl-esters [30]. Rigorous saponification of bile acids, as described by Grundy et al [31], was not necessary because in healthy subjects no conjugated bile acids are detectable in faeces [32]. Further, Lepage et al [33] found that rigorous alkaline hydrolysis of keto bile acids gives low recoveries and formation of bile acid artefacts to a high degree.…”
Section: Collection Of Faeces and Preparation Of The Faecal Extractsmentioning
confidence: 99%
“…This will give similar results, but will prevent the potential formation ofbile acid ethyl-esters [30]. Rigorous saponification of bile acids, as described by Grundy et al [31], was not necessary because in healthy subjects no conjugated bile acids are detectable in faeces [32]. Further, Lepage et al [33] found that rigorous alkaline hydrolysis of keto bile acids gives low recoveries and formation of bile acid artefacts to a high degree.…”
Section: Collection Of Faeces and Preparation Of The Faecal Extractsmentioning
confidence: 99%